Taḥlīl Tanfīdh Barāmij al-Lughah al-‘Arabiyyah fī Ma‘had Dār al-Salām al-Ḥāfiẓ Kinālī Asam Atas, Kota Baru, Jambi: تحليل تنفيذ برامج اللغة العربية في معهد دار السلام الحافظ كينالي أسام أتاس، كوتا بارو، جامبي - Albaroqah, Muhammad; Huda, Rofiazka Fahmi; Helty (Institut Muslim Cendekia, 2025)
This study aims to examine the implementation of the Arabic language program at Pondok Pesantren Darussalam Al-Hafidz in Jambi City and analyze the supporting and inhibiting factors in its execution. Using a descriptive qualitative approach through observation, interviews, and documentation, the research involved the pesantren leader, the head of the language division, teachers, and students as informants. The findings reveal that the implementation of the Arabic language program is well-structured and effective through intracurricular, extracurricular, and daily language immersion activities such as daily vocabulary enrichment, muhadharah (speech practice), qira’ah (reading), and conversational exercises, all of which significantly enhance students’ Arabic proficiency. Supporting factors include strong leadership and teacher commitment, student motivation, a conducive language environment, and the availability of simple yet effective learning media. Meanwhile, the inhibiting factors consist of limited facilities, variations in students’ abilities, time constraints, and inconsistent use of Arabic outside the classroom. Overall, the program contributes positively to improving students’ academic and communicative competence in Arabic and may serve as a valuable reference for Islamic educational institutions in developing more effective and sustainable Arabic language learning strategies.